2000
DOI: 10.1093/emboj/19.10.2181
|View full text |Cite
|
Sign up to set email alerts
|

A complex of mammalian Ufd1 and Npl4 links the AAA-ATPase, p97, to ubiquitin and nuclear transport pathways

Abstract: The AAA‐ATPase, p97/Cdc48p, has been implicated in many different pathways ranging from membrane fusion to ubiquitin‐dependent protein degradation. Binding of the p47 complex directs p97 to act in the post‐mitotic fusion of Golgi membranes. We now describe another binding complex comprising mammalian Ufd1 and Npl4. Yeast Ufd1p is required for ubiquitin‐dependent protein degradation whereas yeast Npl4p has been implicated in nuclear transport. In rat liver cytosol, Ufd1 and Npl4 form a binary complex, which exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
407
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(419 citation statements)
references
References 45 publications
11
407
0
1
Order By: Relevance
“…76,77 Ubiquitination machinery similar to that of yeast is also employed, and a homolog of Cdc48p, termed p97, has been shown to cooperate with mammalian homologs of Ufd1p and Npl4p in substrate dislocation. [78][79][80] Recently, two groups using independent functional criteria identified Derlin1 as a mammalian homolog of Der1p and demonstrated that it mediates the association of p97 with the ER membrane to facilitate ERAD. 81,82 Another protein in this p97 targeting complex, VIMP, was also identified in one of these studies.…”
Section: Esr In Mammalsmentioning
confidence: 99%
“…76,77 Ubiquitination machinery similar to that of yeast is also employed, and a homolog of Cdc48p, termed p97, has been shown to cooperate with mammalian homologs of Ufd1p and Npl4p in substrate dislocation. [78][79][80] Recently, two groups using independent functional criteria identified Derlin1 as a mammalian homolog of Der1p and demonstrated that it mediates the association of p97 with the ER membrane to facilitate ERAD. 81,82 Another protein in this p97 targeting complex, VIMP, was also identified in one of these studies.…”
Section: Esr In Mammalsmentioning
confidence: 99%
“…Article and publication date are available at www.molbiolcell.org/cgi/doi/10.1091/mbc. E03-02-0097.1997), Ufd1/Npl4 (Meyer et al, 2000(Meyer et al, , 2002, VCIP135 (Uchiyama et al, 2002), and SVIP (Nagahama et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…These include roles in ubiquitin-and proteasome-dependent degradation of cytosolic proteins (Ghislain et al, 1996;Dai et al, 1998;Dai and Li, 2001), ER-associated degradation (ERAD; reviewed in Bays and Hampton, 2002;Tsai et al, 2002), and regulated ubiquitindependent processing (Rape et al, 2001 1997), Ufd1/Npl4 (Meyer et al, 2000(Meyer et al, , 2002, VCIP135 (Uchiyama et al, 2002), and SVIP (Nagahama et al, 2003). Although the mechanism by which AAA ATPases such as NSF and p97 use ATP to modulate the structure of their substrates is not known, the overall homology between these two enzymes makes the idea that they might operate by a similar mechanism attractive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VCP has been associated with several essential cell protein pathways 11 : cell cycle, homotypic membrane fusion, nuclear envelope reconstruction, postmitotic Golgi reassembly, DNA damage response, suppressor of apoptosis and ubiquitin-dependent protein degradation [12][13][14][15][16][17][18] . VCP also binds to expanded polyglutamine (poly-Q) protein aggregates 18,19 .…”
mentioning
confidence: 99%